If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + 13 = 5z + 5 Reorder the terms: 13 + 6z = 5z + 5 Reorder the terms: 13 + 6z = 5 + 5z Solving 13 + 6z = 5 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 13 + 6z + -5z = 5 + 5z + -5z Combine like terms: 6z + -5z = 1z 13 + 1z = 5 + 5z + -5z Combine like terms: 5z + -5z = 0 13 + 1z = 5 + 0 13 + 1z = 5 Add '-13' to each side of the equation. 13 + -13 + 1z = 5 + -13 Combine like terms: 13 + -13 = 0 0 + 1z = 5 + -13 1z = 5 + -13 Combine like terms: 5 + -13 = -8 1z = -8 Divide each side by '1'. z = -8 Simplifying z = -8
| 64=24*1+0.10x | | -8-(-3)-4= | | [7(b+4)-16]-[2(b-4)+3]= | | x*x+3600=3721 | | 6*5=10*x | | -7(-4y-19)+15=-2(-9y+16) | | 0.5+2x=3x-0.5 | | 6x^4-12x^3+18x^2=0 | | 27x-35=105 | | x-.2=96 | | 2x+3(-4)=-4 | | 22x+25=6(3x+3)+4x+7 | | 4y-9=5y-5 | | 11v-8v=18 | | 2x-54y=-15 | | -2x-3(-6x-11)=-7 | | 59=x+(x+5)+(x+9) | | 5(3+1)(m-5)= | | 27-(-4)+2= | | 5b+3-2b=12 | | 3(2x-8)-(3X-2)=15 | | 2y=2+8 | | 4y+10=4y-10 | | 20x+23y+24z=185 | | -3(t-4)+9t=8t-3 | | x=.1(50+x) | | 7(x-10)=20-9x | | 2z+6+11z+7=90 | | 6z+12=5z+11 | | 3x-x-4x=18 | | -6(5+r)=12 | | 4s+3p=tp-3 |